Media Wordwall: alternatif Peningkatan Motivasi Belajar Anak Usia Dini di KB Santika Arum - Nur’afifa, Dara; Wahyudin, Erik (Mulya Literasi Publishing, 2025)
Fun learning is essential in the world of Early Childhood (AUD). Educators can utilise technology to create engaging learning media. So that during the learning process, children can be motivated. The purpose of this research is to develop media, to determine the feasibility of media and to determine the influence of WordWall learning media. The method used is R&D (Research and Development) with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The population in this study is all students of Santika Arum Family Planning, and the sample is taken from 15 people. The data collection techniques used are observation and documentation, with the data obtained in the form of learning. The study's results showed that the majority of children fell into the low category, with a percentage of 33.3%. After being given treatment, post-test data showed that the majority of children were in the high category, with a percentage of 46.6%. Therefore, Wordwall media can be used as one of the learning media to increase AUD learning motivation.